El "final" de las Villae en Hispania : I. la transfornación de las Pars Urbana de las Villae durante la antiguidad tardia - López Quiroga, Jorge; Rodríguez Martin, F. Germán (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
One of the principal questions that has centered the investigation in the last years has been the evolution of the Roman villae during the Late Antiquity. Our main objective in this study will be the analysis of the transformation in the pare urbana of the roman villae from 400 to 700 A.D. in Hispania. First, a general approach from some very well-known and documented exemples selected among the great number of villae in Hispania; second, the date obtained will be contrasted with those corresponding to a more reduced territorial environment: the basin of Guadiana river (west of Emerita Augusta); finally, the analysis of a villae, Torre Águila (Montijo, Badajoz), located in the half bassin of the Ana river, a very good exemple of the changes and transformations that the Christianization process will introduce in the roman villae.